The age dependent progression of Hajdu-Cheney syndrome in two families - Jirečková, Jitka; Magner, Martin; Lambert, Lukáš; Baxová, Alice; Leiská, Alena; Kopečková, Lenka; Fajkusová, Lenka; Zeman, Jiří (Prague Medical Report, 2018)
Hajdu-Cheney syndrome (HCS) is a rare multi-system disease with autosomal dominant inheritance and skeletal involvement, resulting mostly in craniofacial dysmorphy with mid-face hypoplasia, dental anomalies, short stature, scoliosis, shortening of the digits and nail beds, acro-osteolysis and osteoporosis. We report the progression of clinical and radiographic findings in five patients with Hajdu-Cheney syndrome from two families. A custom capture array designed to capture exons and adjacent intron sequences of 230 selected genes were used for molecular analyses, and the pathogenic variants identified were confirmed by PCR and Sanger sequencing. In both families we observed age-dependent changes in the disease, with a progression of pain in older patients, a shortening of digits and nail beds on both the hands and feet, kyphoscoliosis and the persistence of Wormian bones in lambdoid sutures. Molecular analyses performed in two patients revealed that they are heterozygotes for a c.6255T>A (p.Cys2085*) variant in the NOTCH2 gene, resulting in a premature stop-codon. Bone mineral density (Z-score < -2) did not improved in a girl treated with calcium and vitamin D supplementation during childhood and bisphosphonate during adolescence. Hajdu-Cheney syndrome is a slowly progressive disease with a frequently unfavourable prognosis in elderly patients, especially for the development of dental anomalies, osteoporosis and the progression of skeletal complications requiring orthopedic surgeries.
Keywords: Female; dítě; ženské pohlaví; kostní denzita; Adolescent; Bone Density; lidé; Osteoporosis; prognóza; Hajdu-Cheney syndrom; progrese nemoci; Aged; Disease Progression; mladiství; Prognosis; Child; senioři; osteoporóza; Hajdu-Cheney Syndrome; Humans